Chapter 23 Care Coordination, Samhandling and Patient Safety - Storm , Marianne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This chapter focus on Norwegian healthcare policies and regulations for care coordination and patient safety. The Norwegian Coordination Reform implemented in 2012 emphasizes patient engagement, care pathways, and competence development in municipal healthcare services. Moreover, protocols for division of work tasks and collaboration between specialist and municipal healthcare services are key aspects. The reform identifies fragmented health services and the lack of coordinated care as main challenges. The authors introduce the concepts of care coordination, continuity of care and patient handovers, and relate these to patient safety. Results from a Norwegian observational study, identifying factors affecting care coordination and patient safety in care transitions between hospital and municipal care, are presented. Finally, the authors introduce relevant measures to improve care coordination and patient safety, including the regulatory work and follow-up of health services through nationwide audits performed by the Norwegian Board of Health Supervision."